Screening and Summary Procedures in the United States Courts of Appeals - Charles R. Haworth (Washington University Law Quarterly, 1973)
The federal intermediate appellate system is on the verge of ceasing to function as an effective administrator of justice. The courts of appeals have therefore taken upon themselves the task of devising methods to speed the flow of cases. These methods, commonly termed screening and summary procedures, involve eliminating or limiting oral argument in selected cases and deciding cases without publishing a written opinion if the court concludes that an opinion would be without precedential value. Although the use of these new procedures in all circuits is considered, emphasis will be on the Fifth Circuit, which has extensively used screening and summary procedures. That circuit instituted its screening procedures in late 1968 and has kept detailed records that facilitate analysis of its experience. The purpose of this Article is to show the need for and extensive use of these procedures and to explore several serious issues raised by their use. Those issues include possible limitations, both statutory and constitutional, on the right of the courts of appeals to eliminate oral argument by local rule, and a suggestion, based on the Fifth Circuit’s experience, that the elimination of oral argument and written opinions may produce an undesirable side effect on the outcome of cases decided in the courts of appeals.
Keywords: Administration of justice; United States – Court of Appeals